THE EFFECT OF BIOCHAR AND MINERAL FERTILIZERS ON PLASTID PIGMENTS CONTENT IN LEAVES OF OKRA: OKRA (Scientific journal of the Fergana State University, 2024)
In the article, the effect of biochar and mineral fertilizers on plastid pigments content in leaves of  okra was studied. Researches were carried out in Net house conditions at the Institute of Genetics and Plant Experimental Biology. Six treatments  were selected during the research: treatment 1 is a control without fertilizer, which was taken to compare the other treatments; treatment 2 is biochar; treatments 3: N80P50K50 kg of mineral fertilizer per hectare; treatment 4: N120P75K75 kg of mineral fertilizer per hectare; treatment 5: mineral fertilizer and biochar (N80P50K50 kg+biochar) and treatment 6: mineral fertilizer and biochar (N120P75K75 kg +biochar) were used. Experiments were conducted in pots containing 8.0kg of soil. The okra plant was grown in a greenhouse for 60 days. The chlorophyll a, chlorophyll b, total chlorophyll and carotenoids content in leaves of okra plant was determined by Hiscox and Israelstam method. According to the analysis of the obtained results, compared to the control, biochar alone treatment increased promoted the chlorophyll a by 16%, chlorophyll b by 14%, total chlorophyll by 16%, and carotenoid contents by 15%. Combination of NPK applications rate (120:75:75 kg/ha) and biochar treatment showed more effective effects on plant. Combination of NPK (120:75:75 kg/ha) and biochar treatment significantly enhanced the chlorophyll a by 49%, chlorophyll b by 57%, total chlorophyll by 52%, and carotenoid contents by 29% in leaves of plant compared to the control.